Correspondence between neurophysiological and clinical measurements of chemotherapy‐induced peripheral neuropathy: secondary analysis of data from the CI‐PeriNomS study. Issue 2 (June 2014) - Griffith, Kathleen A.; Dorsey, Susan G.; Renn, Cynthia L.; Zhu, Shijun; Johantgen, Mary E.; Cornblath, David R.; Argyriou, Andreas A.; Cavaletti, Guido; Merkies, Ingemar S. J.; Alberti, Paola; Postma, Tjeerd J.; Rossi, Emanuela; et al.
Abstract Chemotherapy‐induced peripheral neuropathy (CIPN) lacks standardized clinical measurement. The objective of the current secondary analysis was to examine data from the CIPN Outcomes Standardization (CI‐PeriNomS) study for associations between clinical examinations and neurophysiological abnormalities. Logistic regression estimated the strength of associations of vibration, pin, and monofilament examinations with lower limb sensory and motor amplitudes. Examinations were classified as normal (0), moderately abnormal (1), or severely abnormal (2). Among 218 participants, those with class 1 upper extremity (UE) and classes 1 or 2 lower extremity (LE) monofilament abnormality were 2.79 (95% confidence interval [CI]: 1.28–6.07), 3.49 (95%CI: 1.61–7.55), and 4.42 (95%CI: 1.35–14.46) times more likely to have abnormal sural nerve amplitudes, respectively, compared to individuals with normal examinations. Likewise, those with class 2 UE and classes 1 or 2 LE vibration abnormality were 8.65 (95%CI: 1.81–41.42), 2.54 (95%CI: 1.19–5.41), and 7.47 (95%CI: 2.49–22.40) times more likely to have abnormal sural nerve amplitudes, respectively, compared to participants with normal examinations. Abnormalities in vibration and monofilament examinations are associated with abnormal sural nerve amplitudes and are useful in identifying CIPN.